Effects of AL-Qutub (Tribulus terrestris) on the Spermatogenesis of the Mouse Testis: Histological, Histochemical and Morphometrical Studies - Al-Yawer, Malak; Hassan, Ahmed J.; Haddad, Fara’id Y.S.; Al-Anee, Hakeem; Al-Khateeb, Ekbal (Journal of the Faculty of Medicine Baghdad, 2008)
Backgrounds: Tribulus terrestris is one of the traditional herbs that have a revolutionary breakthrough in the management of erectile dysfunction andhave become world –wide as an “instant treatment”Materials & Methods: Tribulus terrestris was given daily to mature male mouse in a dose of 2 mg /kg body weight for 14 days .10% formalin fixedparaffin sections were performed for histological, histochemical and morphometrical studies.Results: Histological and histochemical studies demonstrated a considerable increase in the number of spermatocytes, spermatids and sperms in parallelwith an increase number of interstitial (Leydig) cells. Morphometrically, the thickness of seminiferous tubule is significantly increased together with asignificant increase in the number of interstitial cells.Conclusions: Tribulus terrestris increases the number of Leydig cells, and the androgens produced by these cells are directly responsible for enhancedspermatogenesis.